Marital Sorting and Inequality: How Educational Categorization Matters - Frederik Almar; Benjamin Friedrich; Ana Reynoso; Bastian Schulz; Rune Vejlin (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper revisits the link between education-based marriage market sorting and income inequality. Leveraging Danish administrative data, we develop a novel categorization of marriage market types based on the starting wages and wage growth trajectories associated with educational programs: ambition types. We find a substantial increase in sorting by educational ambition over time, which explains more than 40% of increasing inequality since 1980. In contrast, sorting trends are flat with the commonly used level of education. Hence, the mapping between education and marriage-market types matters crucially for conclusions about the role of marital sorting in rising income inequality.
Keywords: 330; Ehe; Partnerwahl; Bildungsniveau; Bildungsabschluss; Einkommensverteilung; Theorie; Dänemark